2014
DOI: 10.7785/tcrt.2012.500355
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Single Fraction Stereotactic Ablative Radiotherapy for Lung Metastases

Abstract: Stereotactic Ablative Radiotherapy (SABR) has been previously investigated as an alternative to thoracic surgery in patients with a limited number of pulmonary nodules from different primary tumors. We here report the clinical outcomes of a series of consecutive patients homogenously selected and treated with single dose SABR in our Institution. Eligibility criteria were: 1-5 lung metastases, maximum tumor diameter 50 mm, absent or controlled extra-thoracic disease, adequate pulmonary function, no prior radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 12 publications
5
40
2
1
Order By: Relevance
“…These data are coherent with previous personal ones as reported in [15]. Moreover, Filippi and coworkers in a very recent paper [16] treated 56 and 34 lung lesions by threedimensional conformal radiotherapy and image-guided radiotherapy-VMAT, respectively. The authors used a single dose of 26 Gy prescribed to the 80% isodose and, with a median follow-up time of 24 months, observed progression at the SRS site in 10 lesions (11.1%) and actuarial local control rates at 1 and 2 years were 93.4 and 88.1%, respectively [16].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These data are coherent with previous personal ones as reported in [15]. Moreover, Filippi and coworkers in a very recent paper [16] treated 56 and 34 lung lesions by threedimensional conformal radiotherapy and image-guided radiotherapy-VMAT, respectively. The authors used a single dose of 26 Gy prescribed to the 80% isodose and, with a median follow-up time of 24 months, observed progression at the SRS site in 10 lesions (11.1%) and actuarial local control rates at 1 and 2 years were 93.4 and 88.1%, respectively [16].…”
Section: Discussionsupporting
confidence: 90%
“…This result was probably related to the use of relatively small doses according to the first phase of the dose-escalation study. However, a preliminary comparison of acute pulmonary toxicity seemed encouraging (grade 1 lung: 9.2%) and comparable with data (10.4%) reported by Filippi et al [16]. Moreover, the analysis of quality of life and fatigue-related indicators before and after treatment showed that SRS-VMAT was not associated with any detrimental effects.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…On multivariate analysis, a disease-free interval longer than 24 months was close to significance for a benefit in Cancer-Specific Survival. 22 Osti et al analyzed data from selected patients with 1-5 lung …”
Section: Single Fractionmentioning
confidence: 99%
“…Úgynevezett volumetrikus ívterápiát (VMAT) alkalmazva a nagy dózisú kezelések átlagosan mindössze 6-7 percig tartottak [11]. Filippi és mtsai 102 tüdőáttétes beteget egyszeri 26 Gy dózisú sugársebészeti ellátásban részesítve 93%-os 1 éves lokális kontrollt jeleztek, de grade 3 korai és késői mellékhatásokat leírva [22]. Osti és mtsai 66 tüdőáttétes betegnél 23, illetve 30 Gy egyszeri dózisokat alkalmazva 89%-os 1 éves lokális kontrollt és 12 hónapos medián teljes túlélést értek el [23].…”
Section: áBraunclassified